PENGGUNAAN GAME EDUKASI DIGITAL DALAM PEMBELAJARAN TEOREMA PYTHGORAS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SMP - Safitri, Yeni; Setiawan, Rudy; Wijaya, Elita Mega Selvia (Universitas Tribhuwana Tunggadewi, 2024)
This study aims to determine the effectiveness of using the digital educational game Zep Quiz to improve students’ learning independence on the Pythagorean Theorem topic in eighth-grade junior high school. The method used was a pre-experimental design with a one-group pretest–posttest model involving 21 students from SMP Islam Hasanuddin. Data were collected through learning achievement tests and student perception questionnaires. The results showed an increase in the average score from 57.62 on the pre-test to 78.09 on the post-test, representing a 36% improvement. The questionnaire results also revealed positive student perceptions toward the digital game-based learning media, indicating that it is engaging, interactive, and helpful in understanding mathematical concepts. Therefore, Zep Quiz is considered effective in enhancing students' independent learning skills and mathematics achievement in the Pythagorean Theorem topic.